Do macroeconomic conditions and oil prices influence corporate risk-taking? - Gupta, Kartick; Krishnamurti, Chandrasekhar (Journal of Corporate Finance, 2018)
Oil price is a key direct and indirect factor in the cost of production and strongly influences the future cash flows, investment and revenue of a firm. Although many studies investigate the relationship between oil prices and corporate performance, limited evidence exists on how the oil prices influence corporate risk-taking. Using 190,490 firm-year observations covering 56 countries and spanning 1990 to 2013, we find that firms become risk-averse with rising oil prices. However, this relationship is conditional on the macroeconomic outlook. We show that with rising oil prices, firms increase (decrease) risk-taking if the macroeconomic outlook is favorable (unfavorable). Finally, firms operating in non-competitive industries tend to increase risk-taking with rising oil prices and favorable macroeconomic conditions. Our results are robust to controls for unobserved heterogeneity and alternate modelling procedures to deal with the nested nature of our data.